High-Quality Donor: Criteria for the Selection of Gamete Donors in the Russian Field of Assisted Reproductive Technologies - Grishanina, Anastasia; NarskayaAlexandra; Smirnova, Polina (Journal of Economic Sociology, 2021)
The emergence of assisted reproductive technologies (ARTs) has been one of the groundbreaking solutions to the problem of infertility, but these technologies involve interference with the natural process of giv¬ing birth to a child. In this study, we answer the question of whether we can talk about attempts by parents to influence the "quality" of their child in ART through the mechanism of choosing gamete donors. The theoretical analysis considers the concept of the "quality" of biomaterial in the context of the commodification of vital goods as well as the problem of kinship associated with the transformation of family relations as a result of the application of ARTs. Foreign studies have confirmed the attempt to influence the "quality" of the child through the choice of donors with certain characteristics. However, in the Russian context of social conservatism, previous studies have found interference in the ge¬netics of a child to be unacceptable. The aim of this work is to explore how the possibilities of controlling the "quality" of a child are distributed between doctors and infertile couples as well as the hidden social grounds behind the criteria used for choosing a donor. The focus of the study is on the representatives of reproductive centers and sperm and egg banks in Moscow. The strategies for selecting respondents were targeted selection and the snowball method, with the database consisting of fifteen semi-struc¬tured interviews. The analysis revealed that potential parents are included in the ART process as actors whose actions are subordinate to those of medical centers . The image of a "high-quality" donor is formed through the prism of certain requirements put forward to donors by ART centers and then transmitted to parents. In addition, the study found a tendency in the desire of potential parents to influence the "quality" of their child—not in an absolute but a relative sense—to have a child of the same "quality" as themselves.